Evaluation of Swedish youth labour market programmes - Laura Larsson (Institute for Labour Market Policy Evaluation (IFAU), 2000)
This paper evaluates and compares the direct effects of two Swedish active labour market programmes for youth, namely youth practice and labour market training. Effectiveness of the programmes is measured by subsequent annual earnings, re-employment probability, and probability of regular education. A non-parametric matching approach based on conditional independence assumption is applied to estimate the average program effects. Moreover, the results obtained by matching are compared to results from standard linear regression and probit models, and a polychotomous selectivity model with unobserved individual heterogeneity. The results indicate either zero or negative effects of both programmes in the short run, whereas the long-run effects are mainly zero or slightly positive. The results suggest furthermore that youth practice was better than labour training. However, there is much heterogeneity in the estimated treatment effects among the individuals.
Keywords: C14; C50; J38; J68; 330; Active labour market policies; Balancing score; Evaluation; Matching; Propensity score; Selection; Treatment effects